Manajemen Strategik Guru Dalam Pengelolaan Kelas Dalam Peningkatan Efektivitas Belajar Siswa Di MTs SKB3 Menteri Pembangunan Desa Lidah Tanah - Fatimah Azzahra Lubis; Abdul Fattah Nasution (Universitas Pakuan, 2026)
Strategic Management of Teachers in Classroom Management in Increasing the Effectiveness of Student Learning at MTs SKB 3 Minister of Village Development of Lidah Tanah This study aims to examine the strategic management practices employed by teachers in classroom management and their impact on student learning effectiveness at MTs SKB 3 Menteri Pembangunan, Lidah Tanah Village. The method used was a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data were analyzed through the stages of reduction, presentation, and drawing conclusions using triangulation techniques. The results of this study indicate that teachers' strategic management has been implemented through the planning, implementation, and evaluation stages, but has not been fully optimized due to a lack of consideration of individual student needs. Student learning effectiveness is evident in the level of student activity and ability to complete assignments, although this is not uniform across all students. Influencing factors include teacher competence, student characteristics, the availability of infrastructure, and school support. Therefore, it can be concluded that teachers' strategic management is quite good, but still requires strengthening, especially in the implementation of differentiated learning and evaluation systems to improve student learning effectiveness.